Detection and clinical significance of circulating tumor cells in colorectal cancer - Miao Jiang (BMC, 2021)
Abstract Histopathological examination (biopsy) is the “gold standard” for the diagnosis of colorectal cancer (CRC). However, biopsy is an invasive method, and due to the temporal and spatial heterogeneity of the tumor, a single biopsy cannot reveal the comprehensive biological characteristics and dynamic changes of the tumor. Therefore, there is a need for new biomarkers to improve CRC diagnosis and to monitor and treat CRC patients. Numerous studies have shown that “liquid biopsy” is a promising minimally invasive method for early CRC detection. A liquid biopsy mainly samples circulating tumor cells (CTCs), circulating tumor DNA (ctDNA), microRNA (miRNA) and extracellular vesicles (EVs). CTCs are malignant cells that are shed from the primary tumors and/or metastases into the peripheral circulation. CTCs carry information on both primary tumors and metastases that can reflect dynamic changes in tumors in a timely manner. As a promising biomarker, CTCs can be used for early disease detection, treatment response and disease progression evaluation, disease mechanism elucidation, and therapeutic target identification for drug development. This review will discuss currently available technologies for plasma CTC isolation and detection, their utility in the management of CRC patients and future research directions.